Antibody Response to Pertussis Vaccine Among Children and Adolescents in Croatia: A Cross-Sectional Prevalence Study - Vedran Stevanović; Oktavija Đaković Rode; Goran Tešović (Vaccines)
Background/Objectives: The current national vaccination program does not completely control the transmission of Bordetella pertussis in Croatia. This cross-sectional seroprevalence study aimed to measure the prevalence of IgG antibodies to pertussis toxin (IgG-anti-PT) in regularly vaccinated Croatian children of 6–18 years of age and to estimate the duration of pertussis vaccine-induced immunity elicited by the National Immunization Program (NIP) with respect to the transition from a mixed acellular pertussis (DTaP) and whole-cell pertussis (DTwP) vaccine regimen to a DTaP regimen. Materials and Methods: Single-serum IgG-anti-PT concentrations were measured using a commercial enzyme-linked immunosorbent assay (ELISA) and analyzed in twelve age groups from 2020 to 2023. According to the manufacturer’s classification, IgG-anti-PT concentrations of <40 IU/mL, 40–100 IU/mL, and >100 IU/mL were considered negative, borderline, and positive, respectively. Results: In total, 1314 sera samples were collected and analyzed. Most subjects had an IgG-anti-PT concentration < 40 IU/mL (95.1%). This study sample’s IgG-anti-PT geometric mean concentration (GMC) was very low. Despite different vaccination backgrounds, the waning of IgG-anti-PT concentration was observed in Croatian children and adolescents. Discussion: In the present study, 0.53% of subjects were seropositive (>100 IU/mL). Regardless of the low quantity of IgG-anti-PT, we estimated that a degree of protection against pertussis persisted for at least 8–9 years based on a small increase in IgG-anti-PT GMC in 15–18-year-olds, indicative of an ongoing B. pertussis circulation in Croatia. Although introducing a booster pertussis vaccine could be suitable for young adolescents to strengthen their immunity, before such a recommendation, it would be useful to initiate further research to complement the results obtained in this study.